IMPLEMENTASI DATA MINING DENGAN METODE POHON KEPUTUSAN ALGORITMA ID3 UNTUK MEMPREDIKSI PENJUALAN PADA CV. MITRA BAJA CEMERLANG - Winda Nia Purba; Demak Situmorang; Yulia Alfani; Delima Hutabarat; Fransiskus William Anggiono (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2019)
This study aims to determine the inventory control carried out by CV. Pematangsiantar Shining Steel Partners. The data used in this study are secondary data sourced from company records for the last 3 months. The data analysis method used in this study is the Decision Mining Data Tree method with ID3 algorithm. Through the application of data mining CV. Cemerlang Steel Partners will know more about the items that are of interest to consumers and items that are not in demand, so there will be no more stockpiles that accumulate in the warehouse. The results of this study found that the Root Node in determining which items are in demand and not in demand is the Size attribute. Rule obtained as many as 14 rules, which consists of 7 rules that are worth yes and 7 rules that have no value.